A Multiple-Criteria Analysis Application for Vertical Coordinatıon in the Transportation of Agricultural Commodities in Brazil. Issue 6 (17th August 2016) - Roulet, Michel Camacho; Caixeta-Filho, José Vicente; Yoshizaki, Hugo Tsugunobu Yoshida
ABSTRACT: The strategies used to perform the transportation of agricultural commodities by truck in Brazil are a challenge to decision-making. This article brings together the widely held theories vertical coordination and decision analysis to present a discussion of decision-making in organizations. From a model capable of processing main objectives, multiple criteria, and variables found in transport verticalization problems, the results showed worse performance than hybrid or outsourced alternatives. These results support that in environments with high dependence on low costs and asset specificity, they are no more likely to meet hybrid structures or market coordination. As the price difference between the outsourced and vertical model decreases, there is a preference for hierarchical structure, given its better performance related to the benefits offered. Changes in the institutional environment, such as transport regulations, may modify competitive arrangements. This type of preference by decision-makers for vertical structures could allow larger scale in conjunction with strategies by shippers, as operation costs remain close to those charged by carriers.